Manufacturing of tinidazole by recovering and recycling catalyst - Dongare, Mohan K.; Chandorkar, J. G.; Rode, C. V. (Asian Journal of Chemistry, 2008)
In this paper, the recycle process of tungstic acid by recovering it from waste during the manufacture of tinidazole is described. The recovered tungstic acid gives desired quality and quantity of tinidazole.
Keywords: Recovery; tinidazole; tungstic acid

Montmorillonite for selective hydroxyalkylation of p-cresol - Garade, Ajit C.; Mate, Vivek R.; Rode, C. V. (Applied Clay Science, 2009)
Performances of montmorillonite titanium silicate (TS-1) and dodecatungstophosphoric acid (DTP) were compared for the hydroxyalkylation of p-cresol into dihydroxydiarylmethane (DAM). Ammonia TPD studies of various catalysts showed that an appropriate combination of both strong and weak acid sites of montmorillonite was mainly responsible rather than only the stronger acidity of bulk DTP for its highest catalytic activity for selective hydroxyalkylation of p-cresol to DAM. The selectivity to DAM could be enhanced by adjusting reaction conditions like mole ratio of p-cresol to formaldehyde, reaction temperature, catalyst concentration, solvent and reaction time. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ammonia TPD; Dihydroxydiarylmethane; Hydroxyalkylation; Montmorillonite; Solid acids

Metal cation-exchanged montmorillonite clay as catalysts for hydroxyalkylation reaction - Jha, Ajay; Garade, Ajit C.; Shirai, M.; Rode, C. V. (Applied Clay Science, 2013)
Several solid acid catalysts were prepared by exchanging metal cations such as Zn2+, Fe3+ and Al3+ with montmorillonite clay. Among these, Al-montmorillonite showed the highest acidity determined by the pyridine-IR as well as NH3-TPD methods. A systematic comparison of the performance of these catalysts along with parent montmorillonite was carried out for the hydroxyalkylation of p-cresol with formaldehyde to give 2, 2'-methylenebis (4-methyl phenol) (DAM). It was found that the activity of these catalysts was in accordance with the increase in acidity of parent montmorillonite after the exchange of cations in the order of Zn2+, Fe3+ and Al3+. The selectivity pattern was also influenced by the exchanged cations. Since Al-montmorillonite showed the highest conversion of 51% with 98% selectivity to DAM, the effects of various reaction parameters, namely, mole ratio, catalyst concentration, temperature, reaction time on conversion and selectivity pattern were also studied using the same catalyst This catalyst also showed an excellent stability as evidenced by its eight times reuse. (C) 2012 Published by Elsevier B.V.
Keywords: Cations-exchanged clay; Montmorillonite; NH3-TPD; Pyridine-IR